(untitled) (Journal of the College of Basic Education, 2025)
Although the synthesis of metal nanoparticles using plant extracts and the study of their effects is a relatively new topic, maize contains a wide range of secondary metabolites with high reductive potential, which can be used in a green way for the biosynthesis of silver nanoparticles. The aim of this research is to conduct a phytochemical analysis of the aqueous extract of yellow corn seeds and the biosynthesis of silver nanoparticles using this extract. The optimal conditions for the synthesis of these nanoparticles were also determined, as was the evaluation of the biological activity of the extract and the resulting silver nanoparticles. A silver nitrate solution was prepared at a concentration of (1) mol and a mass of (0.0162) and dissolveed in. 100 ml, of deioniized wateer too preparee the silveer nitrate, solution. (5) ml of the prepared plant extract was slowly added by taking 10 grams of dried and ground yellow corn seeds with 100 ml of deionized water. The solution was placed in a conical flask and boiled for 10 minutes. It was left at room temperature. The plant extract was then filtered and centrifuged several times at 10,000 rpm. It was added gradually, at room temperaturee and, heated on a ,rotating magnetice heater for 24 hours. The synthesis process was completed by changing the color of the extract combined with the ,silveer nitrate, solutiion froms yelloow too dark brown . The solution was then washed, with distilled wateer. It was ,placed in a centrifuge at 8000 rpm for 10 minutes . The activee components of the, plants were identified and it was, found to contaiin flavonoids, phenols, alkaloids, etc. The silver nanoparticles were detected by ultraviolet spectroscopy, scanning electron microscopy (SEM), XRD, and FT-IR.